Adaptive Capacity of Local Governmental Agencies on Water Shortages Affecting the Local Tourism Industry: A Case Study of Koh Chang Island, Thailand - Tanoamchard, Wanvicechanee; Limjirakan, Sangchan (Richtmann Publishing, 2012)
This research aims to study the capacity of Thai local governmental agencies in addressing water shortage causingvulnerabilbities to the local tourism industry on Koh Chang Island. The objectives of the study includes assessing the economic andsocial vulnerability of local tourism industries having been affected by water shortage caused by climate change and to study thecapacity of the local governmental agencies in dealing with the problems. The research design and data collection techniques employedin this research included documentary research, interview, and field surveys. A series of studies were conducted to disclose certaincritical issues of vulnerability caused by water shortage in the study area and to study the current ways that the local governmentalagencies deal with the problems. The study of Yohe and Tol (2002) regarding determinants of adaptive capacity was applied as datacollection framework to create the interview guides and other tools used in this study. Twenty-four respondents in this study comprisinglocal governmental agencies, local community leaders, and local tourism operators. The finding could be concluded that water shortagein Koh Chang Island would come from climate change, but the most important thing is the lack of knowledge on water managementunder the climage change of the local governmental agencies. Therefore, capacity building of local governmental agencies on climatechange and properly water management should be performed in order to reduce water shortage affecting on tourism industries.